Radar amplitude-range-doppler surface fast calculation on graphics processing units - A. V. Barkhatov; A. S. Kozlov (Известия высших учебных заведений России: Радиоэлектроника)
The paper describes the algorithm of fast calculation of the amplitude-range-Doppler surface. The features of the software implementation of the algorithm are drawn. The nuances of parallel computing of the surface on graphics processing units of the gaming graphics card are shown. The result, the sixteen surfaces parallel computing time for multi-channel radar, is presented.